A conceptual model of ubiquitous language learning environment (ULLE) - Zolkefley, Mohd Khairul Ikhwan; Mohd Tahir, Zurainee; Mohd Lokman, Anitawati; Abd Aziz, Azhar; Md Sharif, Shamsudin (2015)
Ubiquitous learning is a popular option amongst students and educators.The landscape of learning environments, however, has become blurry with the fusion of technology. Recent developments in ubiquitous technologies provide new learning paradigms for learning, which goes far beyond the traditional learning paradigms.This paper proposes a conceptual model for Ubiquitous Language Learning Environment (ULLE).It begins by briefly describing the definition and comparison of characteristics in ubiquitous learning followed by proposing the conceptual model of ULLE.ULLE is an integrated learning environment that combines technical, physical, informational and social settings. ULLE ensures more effective and efficient integration amongst school, home and surrounding environment.The essential elements of this model are the integration and coordination of language school, home and other places where learning can take place anywhere and anytime.The type of interaction in ULLE consists of three main subjects such as the people, the objects in the real world and the artifacts in virtual space. With the implementation of ULLE, anyone could benefit the access to the right language learning knowledge anywhere and anytime using any device at their own convenience.